SISTEM PENJAMINAN MUTU PENDIDIKAN DI MADRASAH - Munjin Munjin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
Quality insurance management in education is one of the keys of success of educationinstitution. MII Sambas is one of Islamic elementary school that can achieve high academicand non academic achievement since the application of quality-based management. Thisresearch was aimed at describing the system of quality education insurance being applied byMII Sambas. The focuses of this research were: a) how the process of quality educationinsurance was applied; b) how the human resources were managed; c) what the productsachieved; d) the obstacles in applying the management.This research used qualitative approach and applied observation as the main methodin collecting data. It was also supported with interviews and documentation.Based on the approach, the subject of this research were: headmaster, teachers andstaff, and heads of sections. The data were analyzed using qualitative analysis, whichincluded data collection, data reduction, display of data, and conclusion.Research findings are: a) the preparation stages of quality management in MII Sambasconsists of planning, organizing, supporting, supervising, advising, and evaluating. Thisstages were applied by buttom-up method; b) job description was made to support optimalperformance of each position; c) education service was focused on the process; d) theposition of leaders were based on performance rather than seniority; e) the salary received byteachers and staff refers to the system of civil servant salary; f) some achievements of thisinstitution are: second rank of Healthy School Championship, third rank of national qualityschool, ISO 9001 sertificate in 2008 on management, and other sertificates as a qualifiededucation institution from Religious Affairs Ministry.Besides the progress that have been achieved, there are still some differences inunderstanding wholistically the concept of quality insurance of education. It may resultedfrom the fact that not all teachers have education background. Moreover, MII Sambas will bea greater institution when it has acceptedstudents with special needs, which has not beenrealized